An Overview of Procedures and Tools for Designing Nonstandard Beam-Based Compliant Mechanisms. (May 2021) - Bilancia, Pietro; Berselli, Giovanni
Abstract: Beam-based Compliant Mechanisms (CMs) are increasingly studied and implemented in precision engineering. Straight beams with uniform cross section are the basic modules in several design concepts, which can be deemed as standard CMs. Their behavioral analysis can be addressed with a large variety of techniques, including the Euler–Bernoulli beam theory, the Pseudo-Rigid Body (PRB) method, the beam constraint model and the discretization-based methods. This variety is unquestionably reduced when considering nonstandard CMs, namely design problems involving special geometries, such as curve/spline beams, variable section beams, nontrivial shapes and contact pairs. The 3D Finite Element Analysis (FEA) provides accurate results but its high computational cost makes it inappropriate for optimization purposes. This work compares the potentialities of computationally efficient modeling techniques (1D FEA, PRB method and chained-beam constraint model), focusing on their applicability in nonstandard planar problems. The cross-axis flexural pivot is used as a benchmark in this research due to its high configurable behavior and wide range of applications. In parallel, as an attempt to provide an easy-to-use environment for CM analysis and design, a multi-purpose tool comprising Matlab and a set of modern Computer-Aided Design/Engineering packages is presented. The framework can implement different solvers depending on the adopted behavioral models. Summary tables are reported to guide the designers in the selection of the most appropriate technique and software framework. Lastly, efficient design procedures that allow to configure nonstandard beam-based CMs with prescribed behavior are examined with two design examples. Highlights: An overview of design strategies for beam-based compliant mechanisms is provided. Modeling techniques are analyzed focusing on their applicability to planar problems. A configurable software framework to be used in design optimization is presented. Efficient procedures for devices with prescribed behavior are discussed.